PENGEMBANGAN MEDIA PEMBELAJARAN PRAKTIK BONGKAR PASANG POMPA SENTRIFUGAL DI POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Ridho Syahputra, Muhamad; Rafly, Rafly; Ariyanto, Ariyanto; Masdani, Masdani (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2025)
Centrifugal pumps are one type of pump that is widely used in industry and everyday life. This learning media is designed to provide a comprehensive understanding of the working principles, components, and applications of centrifugal pumps. In the working principles section, it is explained how centrifugal pumps move fluids using centrifugal force generated by a rotating impeller. Fluids enter through the inlet and are accelerated by the impeller, then released through the outlet with higher pressure. The main components of centrifugal pumps such as impellers, casings, shaft seals, and bearings are also explained in detail. Each component has an important function and role in pump efficiency and performance. In this final project, the author developed a learning media for pump disassembly and assembly to meet the material achievements in the syllabus. The methods used in this final project are data collection, identification of component needs, development of plans, creation of learning media, trial of learning media and implementation. After the development of learning media, it is hoped that the learning of the practical course on pump component disassembly and assembly and repair can be met so as to increase knowledge and understanding as well as skills for students.